Inhaled Insulin: Safety and Appropriate Uses - Cunningham, Muriel (MD Conference Express, 2006)
From a biological perspective, there are many advantages to inhaled insulin: the lung has a large surface area and a thin blood barrier, inhaled administration avoids first pass liver clearance, and transport of the medication is rapid and efficient. From a quality of life perspective, perhaps the biggest advantage of inhaled insulin is its mode of delivery.